Designing a Prototype System for Sales Transaction Reconciliation and Guest Data Management - Agustini, Sherly (YCMM, 2024)
This research focuses on the design and development of a prototype information system for transaction recap and guest data management at PT. XYZ. The research addresses the challenges of data inaccuracies and inefficiencies observed in the current system. The methodology includes a comprehensive literature review, followed by interviews, observations, and the application of the waterfall model for system design. The proposed prototype features a web-based interface designed to streamline transaction recording, data management, and reporting processes. The system aims to enhance operational efficiency and data accuracy. Initial evaluations of the prototype indicate improvements in data management, although further refinements are needed before the system can be fully implemented. This research provides valuable insights into the development of effective information systems tailored to organizational needs.